Analisis Kinerja Keuangan Perusahaan Sektor Pertambangan Antara PMA dan PMDN Di Bursa Efek Indonesia - Abdul Basyith; Ismi Fadillah (MBIA, 2019)
This study aims to compare the financial performance between foreign and domestic mining firms in Indonesia for a period of 2012-2016. Not only comparing the financial performance, this study is also aimed at analyzing the impact of liquidity ratio, solvability ratio and activity ratio on financial performance and at analyzing which ratio provides the highest contribution on the financial performance of foreign and domestic mining firms in Indonesia for a period of 2012-2016. The total sample employed is 15 foreign firms (PMA) and 15 domestic firms (PMDN). The independent variable used is liquidity ratio, solvability ratio and activity ratio in which each proxies used are current ratio (CR), debt to equity ratio (DER) dan total assets turnover (TATO). Meanwhile the dependent variable used is profitability ratio in which proxies used are return on assets (ROA) dan return on equity (ROE). The analysis technique used in this study is independent samples t-test and multiple regression equation. The results reveal that: (1) There is no significance difference of variance value for all variables (CR, DER, TATO, ROA dan ROE) between foreign and domestic firms; (2) Apart from CR, TATO, ROA and ROE, only debt to equity ratio (DER) shows a significance difference for foreign and domestic firms; (3) CR, DER, TATO, ROA and ROE for foreign firms is better than domestic firms; (4)Ccurrent ratio (X1), debt to equity ratio (X2), and total assets turnover (X3) have a positive and significant impact simultaneously on the financial performance for both return on assets (ROA) and return on equity (ROE) for foreign and domestic firms; (5) Total assets turnover (X3) is the only variable providing the highest contribution to the improvement of financial performance for both return on assets and return on equity for foreign and domestic firms.